Factores relacionados con la sexualidad en adolescentes del distrito de Tarapoto - 1992 - Portugal Ríos, Giovana (1993)
This cross-sectional descriptive trial was conducted using information on the spot; encuestandose included a total of 1156 adolescent girls in the age group of 15-19 years old; population that was assigned proportionately using simple random sampling with a maximum error of 2% to the groups corresponding to the secondary schools, colleges and universities in the district of Tarapoto in order to know some aspects of reproductive health of our teenagers. Before starting the field traajo were trained people who participated in the data collection, test pilot fectuo a). For the size and adequate representative sample. b). To assess the adequacy and clarity of each question and identify problem questions. The registration forms were anonymous and the singling out of the sample is allowed. It was found that 62.12% of adolescents are sexually active; the average age of first sexual intercourse is 13.83 years, the level of knowledge about sexually transmitted diseases is bad in 80.40 percent; the average age at which they received sexual education for the first time is 13 years; It is the first school where they receive; the level of knowledge about sexuality is bad in 89.80 percent; only 23.70% of adolescents use contraception, the rhythm method being the most widely accepted with 15.22 percent; the incidence of abortions is 14.27% and the incidence of rape is 3.80 percent.